Cordycepin Alleviates Anterior Cruciate Ligament Transection (ACLT)-Induced Knee Osteoarthritis Through Regulating TGF-β Activity and Autophagy [Retraction] - Tao XM; Liu PF; Gu HY; Lian DB; Gao L; Tao WW; Yan D; Zhao B (Dove Medical Press, 2020)
Tao XM, Liu PF, Gu HY, et al. Drug Des Devel Ther. 2020;14:2809–2817. The Editor-in-Chief and Publisher of Drug Design, Development and Therapy wish to retract the published article. The authors notified us of some potential image duplication in their article:● Figure 1C Control (H&E) appears to be duplicated with Figure 2B Control (H&E) and Figure 4B Control (H&E)● Figure 1C Sham (H&E) appears to be duplicated with Figure 2B Sham (H&E)● Figure 1C Control (Alcian blue) appears to be duplicated with Figure 2B Control (Alcian blue) and Figure 4B Control (Alcian blue)● Figure 1C Sham (Alcian blue) appears to be duplicated with Figure 2B Sham (Alcian blue)● Figure 1C ACLT (H&E) appears to be duplicated with Figure 2B Sham (H&E), Figure 4B Sham (H&E) and Figure 5A Sham (H&E)● Figure 1C ACLT (Alcian blue) appears to be duplicated with Figure 2B ACLT (Alcian blue), Figure 4B ACLT (Alcian blue) and Figure 5A ACLT (Alcian blue)● Figure 2B COR-20+ACLT (H&E) appears to be duplicated with Figure 4B COR-20+ACLT (H&E) and Figure 5A COR-20+ACLT (H&E)● Figure 2B COR-20+ACLT (Alcian blue) appears to be duplicated with Figure 4B COR-20+ACLT (Alcian blue) and Figure 5A COR-20+ACLT (Alcian blue)● Figure 1C Control (H&E) appears to show partial overlap with Figure 1C Sham (H&E) and Figure 2B Sham (H&E)● Figure 1C Control (Alcian blue) appears to show partial overlap with Figure 1C Sham (Alcian blue) and Figure 2B Sham (Alcian blue) Despite notifying the journal of some of the duplicated images the authors were unable to provide a satisfactory explanation for the extent of the duplication. The authors were also unable to provide the original western blot raw data for their study. The editor determined the findings of the study were no longer valid and requested for the article to be retracted. The authors wish to apologise for this error. Our decision-making was informed by our policy on publishing ethics and integrity and the COPE guidelines on retraction. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”. This retraction relates to this paper